Pilot Testing of Peak Alpha Frequency Stability During Repetitive Transcranial Magnetic Stimulation - Petrosino, Nicholas J.; Zandvakili, Amin; Carpenter, Linda L.; Philip, Noah S. (Frontiers in Psychiatry, 2018)
1 Abstract Over half of those diagnosed with posttraumatic stress disorder (PTSD) have comorbid major depressive disorder (MDD), and rates are even higher among military veterans. Transcranial magnetic stimulation (TMS) may be a safe and efficacious treatment for PTSD, both with and without comorbid MDD. Still, the mechanism of action of TMS is not fully understood, and it remains unclear which stimulation techniques (e.g. target regions, pulse strength/frequency, waveform) optimize treatment for these patients. Recent research indicated that a patient’s unique individualized alpha frequency (IAF) may be used to guide brain stimulation treatment, and emerging data suggests that stimulation synchronized to the IAF may be efficacious for MDD. However, to our knowledge there are no studies to date that evaluate the stability of IAF over time in patients with comorbid PTSD and MDD. To this end, we used an eight-lead electroencephalography (EEG) system to record IAF before and after a course of TMS. Stimulation parameters were informed by prior studies of TMS for comorbid PTSD and MDD and included 5Hz TMS to the left dorsolateral prefrontal cortex, at 120% of motor threshold, 3000-4000 pulses per session for up to 40 sessions. We tested whether IAF was changed with a course of TMS therapy and evaluated whether IAF predicted clinical outcomes. We observed no significant changes in IAF from baseline to post-treatment, and there was no relationship between IAF and clinical symptom change. These data demonstrate the stability of IAF with TMS and indicate its utility as a trait marker for future brain stimulation studies. This work does not support the use of IAF as predictor of clinical response to TMS as administered.